Self-diffraction effect observation and recording the holographic one-dimensional and two-dimensional gratings in thin photosensitive films - Ageev, L.A.; Beloshenko, K.S.; Makovetsky, E.D.; Miloslavsky, V.K. (Functional Materials, 2007)
A setup for observation of the nonlinear self-diffraction effect has been described. A semiconductor laser (P≈50 mW, λ≈660 nm) is used as a radiation source. The laser beam is divided into two beams by a Wollaston prism, the beams pass through a polarizer and positive lens, then they intersect and create an interference. Using a microscope, the interference may be observed in an increased scale on a remote screen. The interference is registered in a thin photosensitive As₂S₃—Ag film prepared by vacuum evaporation. We have shown an opportunity to observe the self-diffraction from recorded diffraction grating with linear grooves and from two-dimensional grating induced as a result of second exposure after turning the convergence plane of the interfering beams by 90°.